Scattering of charmed baryons on nucleons - Haidenbauer, J.; Krein, G. [UNESP] (Springer, 2018)
Chiral effective field theory is utilized for extrapolating results on the Lambda N-c interaction, obtained in lattice QCD at unphysical (large) quark masses, to the physical point. The pion-mass dependence of the components that constitute the Lambda N-c potential up to next-to-leading order (pion-exchange diagrams and four-baryon contact terms) is fixed by information from lattice QCD simulations. No recourse to SU(3) or SU(4) flavor symmetry is made. It is found that the results of the HAL QCD Collaboration for quark masses corresponding to m(pi) = 410-570MeV imply a moderately attractive Lambda N-c interaction at m(pi) = 138MeV with scattering lengths of a approximate to -1 fm for the S-1(0) as well as the S-3(1) partial waves. For such an interaction the existence of a charmed counterpart of the hypertriton seems unlikely but four- and/or five-baryons systems with a Lambda(c) baryon could be indeed bound.